Introduction to recombinant enzyme pre-commecialization - Amid, Azura (Springer International Publishing, 2015)
This chapter discusses a number of matters involving the commercialization of recombinant enzymes. The chapter begins with an introduction of recombinant enzymes and an explanation of why they should be commercialized, the factors that encourage academics to commercialize product, the methods that can be used in the commercialization process and the obstacles in the commercialization process.